60 let študija tehnike v Mariboru - Prebevšek , Pia (2021)
60 Years of Technical Studies in Maribor. The publication 60 years of Technical Studies in Maribor describes the development of the Faculty of Electrical Engineering and Computer Science; Faculty of Civil Engineering, Transportation Engineering and Architecture; Faculty of Chemistry and Chemical Engineering and the Faculty of Mechanical Engineering. The content of the publication guides us through an overview of the history and important milestones from the enrollment of the first student to the separation of faculties and the establishment of four new faculties. After we can read a presentation of each faculty. In the last chapter, the publication focuses on the development and description of the operation of the Library of Technical Faculties.
Keywords: higher education; university; historical overview; development; technical studies; study; engineering